Antropossolos e áreas de risco a escorregamentos: estudo de caso na comunidade do Sítio Joaninha (Diadema) e Antigo Lixão do Alvarenga (São Bernardo do Campo) - Região Metropolitana de São Paulo (RMSP) - Santos, Juliana Alves dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
During the summer in 2010, Brazilian communication media (CM) reported the case of landslides which resulted in 267 victims, among which 45 died in Morro do Bumba, Niterói / RJ. Subsequent studies revealed that the phenomenon was due to a combination of factors such as the topographic features, the presence of methane gas, the excessive trash and intense summer rainfall. Similar situations are common in tropical countries such as Brazil. In this research, we highlight the Metropolitan Region of São Paulo (MRSP) where the population of Sitio Joaninha lives. It is located between the municipalities of Diadema and São Bernardo do Campo, this last one housed from 1970 to 2001, an old landfill called Alvarenga, whose environmental liabilities were materialized in Antropossolos Líxicos, on which there are housing nowadays. According to some residents the physical conditions of the land added to the instability of the soil class, landslides have already occurred and spontaneous combustion. In this context, this study aimed to evaluate the social and environmental quality of the study area, directly related to the presence of Antropossolos. To this end, we applied 75 questionnaires with qualitative questions. With an auger of a Dutch design were collected about 2,000 cm3 of land, with 1 meter depth in 5 collection points of a hill in Sítio Joaninha. At the samples collected were identified anthropogenic materials such as glass, plastic, fabric, among others. In Soil Mechanics Laboratory of UNESP/FEA Campus of Bauru, the following characterization tests were conducted: granularity, Atterberg limits or levels of consistency and density of solids (ABNT, 1984)...

No verão de 2010 a mídia brasileira noticiou o caso do escorregamento de terra que resultou em 267 vítimas, dentre as quais, 45 mortes no Morro do Bumba, Niterói/RJ. Estudos posteriores demonstraram que o fenômeno foi resultado da combinação de fatores como as características topográficas, a presença de gás metano, o excesso de lixo e as chuvas intensas do verão. Situações semelhantes são reincidentes em países tropicais como o Brasil. Nessa pesquisa, destaca-se a Região Metropolitana de São Paulo (RMSP) onde vive a população do Sítio Joaninha, entre os municípios de Diadema e São Bernardo do Campo, sendo que este último abrigou de 1970 a 2001, o antigo lixão do Alvarenga, cujo passivo ambiental materializou-se na forma de Antropossolos Líxicos, sobre o qual atualmente existem moradias. Em virtude das condições físicas do terreno, somadas à instabilidade dessa classe de solo, já ocorreram escorregamentos e combustão espontânea, segundo alguns moradores. Nesse contexto, o presente trabalho objetivou avaliar a qualidade socioambiental da área de estudo, diretamente relacionada com a presença dos Antropossolos. Para tanto, foram aplicados 75 questionários com perguntas abertas e fechadas. Com um trado do tipo holandês, foram coletadas aproximadamente 2.000 cm3 de terra, a 1 metro de profundidade, em 5 pontos de coleta de uma colina no Sítio Joaninha. Nas amostras coletadas foram identificados materiais antrópicos como vidro, plástico, tecido, entre outros. No Laboratório de Mecânica de Solos da UNESP/FEA Câmpus de Bauru, foram realizados os seguintes ensaios de caracterização: granulometria, Limites de Atterberg ou índices de consistência e massa específica dos sólidos (ABNT, 1984)...
Antroposoils and risk areas landslides: case study on the Sítio Joaninha (Diadema) and Alvarenga's Garbage (São Bernardo do Campo) - metropolitan region of São Paulo
Keywords: Geografia; Deslizamentos (Geologia) - São Paulo, Região Metropolitana de (SP); Urbanização - São Paulo, Região Metropolitana de (SP); Lixo - Estudo de casos - Diadema (SP); Solos - Lixiviação; Geography